2011
DOI: 10.1108/13565361111097083
|View full text |Cite
|
Sign up to set email alerts
|

Temperature cycling analysis for ball grid array package using finite element analysis

Abstract: Purpose -The purpose of this paper is to discuss the capability of finite element analysis (FEA) in performing the virtual thermal cycling reliability test to evaluate the reliability of solder joints in a ball grid array (BGA) package. Design/methodology/approach -Thermal cycling test has been used to evaluate the reliability or fatigue life of the solder joints in BGA package using commercially available FEA software, ANSYSe. The effect of different temperature cycling condition is studied by applying differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…This finding also suggested that the Al width can be relaxed on developing the proposed TEG since it has the least effect on the output power. It is known that the development or manufacturing cost of a product can be reduced when the selected factors have the least accuracy tolerance or for this case the least sensitive factor of Al width [22].…”
Section: Methodsmentioning
confidence: 99%
“…This finding also suggested that the Al width can be relaxed on developing the proposed TEG since it has the least effect on the output power. It is known that the development or manufacturing cost of a product can be reduced when the selected factors have the least accuracy tolerance or for this case the least sensitive factor of Al width [22].…”
Section: Methodsmentioning
confidence: 99%
“…The chosen Kriging uses a Gaussian correlation function and a quadratic basis function. Thus, to build Kriging metamodel, there are n k required points, which are a number of free parameters in quadratic basis function, n k ¼ p ¼ 1 2 ðn þ 1Þðn þ 2Þ. Consequently, the approximate ranking procedure will be performed in case the number of required points is assured, otherwise, the number of points jT j in the training set is more or equal to n k .…”
Section: Proposed Algorithm and Numerical Test 41 Proposed Algorithmmentioning
confidence: 99%
“…Thermal cycling test is one of the most commonly used reliability tests to assess thermo-mechanical reliability of the solder joints. The purpose of this test is to investigate the aptitude of solder joints to support mechanical stresses which is a major failure mechanism that can lead to solder joint fatigue failure [1][2][3][4][5]. The Thermo-mechanical stresses induced by alternating thermal cycles [6] are mainly induced by thermal expansion mismatch of different materials in assembly system.…”
Section: Introductionmentioning
confidence: 99%
“…Solder joints' fatigue life in thermal cycling tests has been studied for decades using the finite element method. While many researchers are investigating the influence of thermal cycling on the reliability, it is still a heating-concerned problem to be discussed [4][5][6][7][8]. Xuejun Fan [9] found that the ramp rate, the dwell time, and the frequency of thermal cycling have a great impact on the reliability.…”
Section: Introductionmentioning
confidence: 99%